2017
DOI: 10.1186/s12906-017-1600-z
|View full text |Cite
|
Sign up to set email alerts
|

Maternal intake of dietary virgin coconut oil modifies essential fatty acids and causes low body weight and spiky fur in mice

Abstract: BackgroundCoconut oil is commonly used as herbal medicine worldwide. There is limited information regarding its effects on the developing embryo and infant growth.MethodsWe investigated the effect of virgin coconut oil post-natally and until 6 weeks old in mice (age of maturity). Females were fed with either standard, virgin olive oil or virgin coconut oil diets 1 month prior to copulation, during gestation and continued until weaning of pups. Subsequently, groups of pups borne of the respective diets were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Echinacea species came from North America and were traditionally used by the Indians for a variety of diseases, including mouth sores, colds, injuries, tooth pain and insect bites [75].…”
Section: Echinacea (Echinacea Spp)mentioning
confidence: 99%
“…Echinacea species came from North America and were traditionally used by the Indians for a variety of diseases, including mouth sores, colds, injuries, tooth pain and insect bites [75].…”
Section: Echinacea (Echinacea Spp)mentioning
confidence: 99%
“…Our previous study also demonstrated the mitigating potential of VCO on HAART‐induced testicular ravages (Ogedengbe et al ., ). Other health benefits of VCO include neuroprotective and memory enhancing abilities (Rahim et al ., ), a cardioprotective potential (Kamisah et al ., ), antidiabetic capacity (Akinnuga et al ., ), hepatoprotective potential (Zakaria et al ., ), and ability to help reduce body weight (Gunasekaran et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…It is my scientist friends (Associate Professors Azlina Ahmad Annuar, Michael Ling King Hwa and Cheah Pike See) have supported me for many years -a network of Malaysian neurobiologists and neuroscientists committed to advancing science and the betterment of life. I have argued with them, debated with them, benefitted endlessly from their kindness and generosity, especially in scientific resources, and published with them (Abdullah et al, 2017;Halim-Fikri et al, 2015;Mansor et al, 2020;Mohd-Zin et al, 2016). They have constantly reminded me to be less of a Mother Teresa and be a little less crazy and perhaps spend a bit more time fulfilling my work KPI.…”
Section: Dealing With Science and Politics Of Malaysiamentioning
confidence: 98%
“…Our labs are the only ones in the country equipped to study mouse embryonic development. We have found coconut oil and red palm olein to be a rather deleterious choices of cooking oil (Gunasekaran et al, 2017). The only oil we know positively affects neural tube closure is a particular Black Seed Oil, given a specific fatty acid distribution (unpublished).…”
Section: Does Maternal Diet Contribute To Neural Tube Defects?mentioning
confidence: 99%